(untitled) (KYAMC Journal, 2020)
Background: Type 2 diabetes is a chronic disease characterized by various metabolic defects. Uncontrolled diabetes mellitus gives rise to a number of life-threatening complications that can increase mortality and morbidity. Objectives: This study was carried out to compare the effectiveness of glycemic control between combined therapy of sitagliptin-metformin and metformin monotherapy. Materials and Methods: Total data of 40 newly diagnosed type-2 diabetic patients were compiled in the study. Those patients having HbA1c more than 6% were considered as uncontrolled diabetes. The total subjects were randomly divided into two experimental groups, treated by metformin alone and treated by sitagliptin-metformin combination. Both groups were treated for three consecutive months and they were followed up after 12 weeks of treatment. Fasting blood sugar (FBS), blood sugar 2 hours after breakfast (2-ABF) and glycated hemoglobin A1c(HbA1c) were estimated in both experimental groups before starting of treatment and after 12 weeks of treatment. Results: HbA1c change from baseline was 0.82% with metformin and 1.83% with sitagliptin-metformin combination. Fasting blood glucose changed from 9.41±1.34mmol/l to 8.04±1.10mmol/l with metformin and from 9.75±1.40mmol to 7.25±0.80 with sitagliptin-metformin therapy. Blood sugar 2hours after breakfast changed from 12.68±1.07mmol/l to 10.34±1.68mmol/l with metformin and from 12.65±1.90mmol to 8.74±0.68 with sitagliptin-metformin therapy. The results showed that though both experimental groups reduced FBS, blood sugar 2-ABF, HbA1c at an acceptable level the combined therapy was found to be superior in terms of effectiveness. Conclusion: The administration of sitagliptin-metformin combined therapy to control hyperglycemia uniquely is preferable. KYAMC Journal Vol. 11, No.-3, October 2020, Page 150-153